2016
DOI: 10.1097/sla.0000000000001853
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Systemic Biomarkers and Cognitive Function Associated with Carotid Revascularization

Abstract: Objective To determine factors affecting cognition and identify predictors of long-term cognitive impairment following carotid revascularization procedures. Background Cognitive impairment is common in older patients with carotid occlusive diseases. Methods Patients undergoing carotid intervention for severe occlusive diseases were prospectively recruited. Patients received neurocognitive testing before, 1, and 6 months after carotid interventions. Plasma samples were also collected within 24 hours after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The correlation between carotid artery stenosis, cognitive function and brain connectivity impairments was described in previous researches. For example, it is known that both CAS and CEA are associated with long-term improvements in cognitive performances [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between carotid artery stenosis, cognitive function and brain connectivity impairments was described in previous researches. For example, it is known that both CAS and CEA are associated with long-term improvements in cognitive performances [45].…”
Section: Discussionmentioning
confidence: 99%
“…Another limit is the use of MMSE as the only test used for the evaluation of the cognitive functions of the patients: cognitive improvements seen after CEA were already demonstrated in previous researches that patients who underwent CEA showed improvements in cognition, mood and quality of life tests [8,45]. Even if MMSE is not the most appropriate test for cognitive analysis in patients with ICA stenosis, it was used as surrogate test in order to give general indications on the trend of neurocognitive performances before and after the surgical procedure due the exploratory intent of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, executive functions measured with the MoCA improved significantly only in patients after CEA, whereas memory measured with the MoCA improved in both the post-CEA and pharmacologically treated groups. In general, both intervention methods improved the MoCA score, but CAS did not cause improvement in any subscale [49].…”
Section: Comparison Of Cas and Ceamentioning
confidence: 80%
“…Zuniga and colleagues also showed that inflammatory biomarkers such as IL-12p40, SDF1-α and TNF correlated with the occurrence of cognitive dysfunction after CEA or CAS (41). When compared with carotid stenting (55 patients), endarterectomy (43 patients) demonstrated postoperative improvement in cognition at one and six months compared with the baseline.…”
Section: Comparison Of the Effects Of Carotid Endarterectomy (Cea) And Carotid Artery Stenting (Cas) Surgerymentioning
confidence: 96%